Gestionar los odios para obtener la paz: paradojas de la construcción de la paz en Colombia; Managing hatred to achieve peace: paradoxes of constructing peace in Colombia - Uribe Sarmiento, John Jairo (Universidad Autónoma Metropolitana, 2019)
Colombian attitudes are analyzed in relation to the peace treaty signed between the government and the Colombian Revolutionary Armed Forced (Fuerzas Armadas Revolucionarias de Colombia farc). For this, related phenomena are examined regarding the plebiscite through which such an agreement was approved or refused: campaign strategies for or against, opinion polls regarding key topics (political participation, coexisting with former combatants), and focus groups discussions. The main argument is that management of hatred and fear have led to a foundation on which to build peace in the country.; Se analizan las actitudes de los colombianos frente al acuerdo de paz firmado entre el gobierno y las Fuerzas Armadas Revolucionarias de Colombia (farc). Para ello se examinan fenómenos relacionados con el plebiscito mediante el cual los ciudadanos aprobaron o no dicho acuerdo: estrategias de campaña en favor o en contra, encuestas de opinión sobre temas cruciales (participación política, convivencia con excombatientes) y discusiones en grupos focales. Se argumenta que la gestión de los odios y los miedos devino el eje para construir la paz en el país.